Maintenance of social order through public signage in the linguistic landscape of Pakistan - Tahir, Samia (2023)
Linguistic landscape, the visibility of languages in public spaces has largely focused on the display of words in the street with respect to multilingualism. Maintaining social order through signboards has very limited research in the linguistic landscape. This study examined the maintenance of social order through public signboards in eight public areas in the linguistic landscape of Pakistan. As a mixed-method study, it first explored linguistic structures on 502 photographed signboards; secondly, linguistic structures beyond the sentence were examined by analysing the interview data obtained from eight local people and data obtained from 64 observation checklists. Thirdly, the discourse of language and power was discussed by scrutinising interview data obtained from the eight authorities. Mediated discourse analysis, as given by Scollon and Scollon in 2003, was used as the theoretical framework. Among the 12 textual genres identified, prohibitory, warning, command and restrictive signboards were found to be highly influential in maintaining social order in a strict way. Though such signboards are necessary to maintain social order but anything domineering hinders rather than helps to achieve the objective. The other two sources of data collection triangulated the study and reaffirmed the results of the primary research. The authorities of the signboards portrayed an ideal picture and put all the blame on the local people, saying they were the ones not following signboards, which elucidated their power as authorities. The local people believed that excess of negation on public signboards had the opposite effect. It makes them even more to disregard what is written on signboards. Conclusively, this study can help to bridge the communication gap between the authorities and sign makers in improving the language of public signboards as it recommends minimising the content of harsh words and replacing them with indirect wordings. It will help authorities to gain their target of maintaining social order more efficiently.